Historic timber repair techniques typology in heritage building conservation; an analysis of Malaysian practice - Muhammad, Afzanizam; Harun, Siti Norlizaiha; Abdul Talib, Yuhainis; Abdul Karim, Norashikin; Abdul Halim, Nurrajwani (2025)
Timber has been an integral part of Malaysia's architectural heritage, contributing to the uniqueness and historical significance of its heritage buildings. As the conservation of heritage structures gains importance, the practice of repairing historic timber elements becomes paramount. This study objectives are (i) to explores the methods, challenges, and significance of historic timber repairs in Malaysian heritage building conservation (ii) to investigates the practice of historic timber repairs in heritage building conservation in Malaysia and (iii) to examine the methods, materials, and approaches employed in historic timber repairs in Peninsular Malaysia. The use of timber in traditional Malaysian architecture has made a significant contribution to the country's architectural heritage. However, the diminishing supply of historic timber resources and traditional knowledge in timber restoration pose increasing challenges to the preservation of this heritage. The research also analyzes the challenges and issues faced by conservation professionals and contractors in their efforts to maintain the structural integrity and historical significance of heritage buildings that incorporate timber elements. Data was collected through an in-depth case study of historic timber repair projects conducted across Malaysia. Data analysis includes a comparison between traditional and modern methods used in restoration, as well as an assessment of the impact of repairs on the authenticity and historical value of the buildings. The findings of this study provide valuable insight into the practice of historic timber repairs in Malaysia and underscore the importance of preserving traditional knowledge in heritage conservation. It also offers practical guidance for conservation professionals and contractors involved in the restoration of historic timber buildings. This research emphasizes the necessity of ensuring that historic timber repairs in Malaysia are carried out meticulously to preserve the authenticity and historical value of the buildings while safeguarding the dwindling resources of timber.